Synthesis, Crystal Structure and Photoluminescence of Cocrystal of Bis(2-(2-hydroxyphenyl)benzimidazolate)zinc and DMF Solvate - Tong, Yi-Ping; Lin, Yan-Wen; Chen, Yan (Asian Journal of Chemistry, 2011)
The Zn(II) complex with 2-(2-hydroxyphenyl)benzimidazole, namely [Zn(2-(2-hydroxyphenyl)- benzimidazolate)2]·2DMF (1·2DMF) has been synthesized and characterized using X-ray crystallography and photoluminescence. The crystal data for this complex is as follows: orthorhombic, space group pbcn, Mr = 630.01, Z = 4, a = 15.405(4) Å, b = 8.818(3) Å, c = 22.068(6) Å, V = 2997.5(15) Å3, Dc = 1.396 g/cm3, μ = 0.867 mm-1, F(000) = 1312, the final R1 and wR2 are 0.0468 and 0.1093 for 2394 unique reflections (I ≥ 2σ(I)) and R1 and wR2 are 0.0755 and 0.1225 for all 14163 reflections. The steady-state and time-resolved photoluminescent spectra for this compound have also been studied. The emission property can be ascribed to π→π* ligandcentered charge transfer transition (LCCT).